A Convex–Concave Procedure-Based Method for Optimal Power Flow of Offshore Wind Farms - Chen, Yuwei; Li, Hongke; Chen, Qing; Xie, Rui; Wang, Xiaohe (Frontiers in Energy Research, 2022)
In recent years, offshore wind farms have boomed all over the world. It is essential to manage the energy dispatch of the offshore wind power systems to reduce transmission losses. This article proposes an optimization method for the optimal power flow of offshore wind power systems based on the convex–concave procedure. First, the nonlinear variables in the power flow constraints of the offshore wind power system are relaxed with newly defined variables. Second, the non-convex constraints are reconstructed according to the variables’ characteristics so that the optimization method satisfies all constraints at the same time. Meanwhile, by applying the Taylor series expansion, the relaxation variables’ gaps are changed dynamically, and the convex relaxation is tightened to ensure the effectiveness of the proposed method. Finally, the feasibility of the relaxation and the optimized solution is verified by the simulation to realize the power optimization in the real offshore wind system.